Stent Grafts Can Convert Unusable Upper Arm Arteriovenous Fistulas into a Functioning Hemodialysis Access: A Retrospective Case Series - Bavare, Charudatta S.; Street, Tiffany K.; Peden, Eric K.; Davies, Mark G.; Naoum, Joseph J. (Frontiers in Surgery, 2017)
Introduction: Not all newly created arteriovenous fistulas (AVF) successfully mature and develop into a functioning access for hemodialysis. Percutaneous transluminal angioplasty (PTA) and balloon-assisted maturation (BAM) have been utilized to either treat flow-limiting stenoses or to promote and accelerate maturation. We hypothesized that unusable upper arm AVFs can be rescued by conversion to a functional access using the percutaneous placement of a stent graft (SG). Methods: Clinical data on 12 patients with an early non-usable upper arm AVF underwent percutaneous revision using stent grafts. There were 6 brachial-cephalic, 3 brachial-basilic, and 3 brachial-brachial vein transposition AVFs. Results: All patients had either at least 2 or more stenoses (> 2 cm) within the fistula conduit, or a long segment stenosis (> 4 cm) in combination with shorter segment stenoses. Nine patients had failed PTA. Three patients had failed BAM at outside access centers. All patients were referred for failure to achieve access cannulation and concomitant hemodialysis through the AVF. Stent grafts were placed retrograde towards the arterial anastomoses and ranged in diameter (6 mm, 7 mm, and 8 mm in 4, 7 and 1 patients, respectively). The average length of the stent graft was 10 cm (range 5-15 cm). All stent grafts were post balloon dilated at the time of placement. All AVFs were salvaged and patients were able to maintain functional use of their access with cannulation occurring through the stent graft. The primary patency (PP) rate at 6 and 12 months was 91% (95% confidence interval (CI), 56% to 98%) and 65% (95% confidence interval (CI), 32% to 87%), respectively (n= 11 and 5 at risk, respectively). The secondary patency (SP) rate at 6 and 12 months was 100 % and 72% (95% confidence interval (CI), 46% to 93%), respectively ( n=11 and 7 at risk, respectively ). Conclusions: This report outlines a successful initial experience using stent grafts to rescue, preserve and convert an unusable upper arm AVF into a functioning hemodialysis access.